Factors related to stunting status of the children aged under two years in Magway Township, Myanmar - Su Wai Phyo (2015)
This cross-sectional analytic study was carried out to determine factors related to stunting status of children aged under two years in Magway Township, Myanmar. Data were collected by using multi-stage cluster sampling and a total of 399 children aged under two years and their mothers were included in this study. After interviewing the mothers by using a face to face method, anthropometric measurements of the children and mothers were performed. Descriptive statistics were used to describe the characteristics of independent variables, dependent variable, and stunting status of the children. Chi-square test and multiple logistic regression were applied to identify the factors related to the stunting status of children. The finding shows that nearly one-fourth of the under two years children (23.8%) were stunted. The result from multiple logistic regression showed that mother’s height (<145 cm), family income (<25 percentile/ <60$), child age (>10 months), gestational age of the child (<37 weeks) and early introducing of complementary food to the children (<6 months) were the predicting factors of the stunting status of the children in this population. Therefore, Maternal and Child Health Care Services, implementing various health education and intervention programs to the mothers and families focusing on quality antenatal care and an appropriate time for introducing complementary food should be addressed.